2012
DOI: 10.1107/s1600536812043620
|View full text |Cite
|
Sign up to set email alerts
|

1-Allyl-1H-1,3-benzimidazol-2(3H)-one

Abstract: The fused five- and six-membered rings in the title compound, C10H10N2O, are approximately coplanar, with an r.m.s. deviation of 0.008 Å. The mean plane of the allyl group is roughly perpendicular to the mean plane of the 1,3-benzimidazol-2(3H)-one system, making a dihedral angle of 86.1 (2)°. In the crystal, each mol­ecule is linked to its symmetry equivalent partner by a pair of N—H⋯O and C—H⋯O hydrogen bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
4

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In a previous study, we reacted benzimidazol-2-one with dodecyl bromide in the presence of a catalytic quantity of tetra-n-butylammonium bromide under mild conditions to form 1-dodecyl-1H-benzimidazol-2(3H)-one (Belaziz et al, 2012;Ouzidan et al, 2011). The study is extended to the synthesis of new benzimidazol-2-one derivative by action of methylbenzyl bromide with 1H-benzimidazol-2(3H)-one to form the title compound (Scheme 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study, we reacted benzimidazol-2-one with dodecyl bromide in the presence of a catalytic quantity of tetra-n-butylammonium bromide under mild conditions to form 1-dodecyl-1H-benzimidazol-2(3H)-one (Belaziz et al, 2012;Ouzidan et al, 2011). The study is extended to the synthesis of new benzimidazol-2-one derivative by action of methylbenzyl bromide with 1H-benzimidazol-2(3H)-one to form the title compound (Scheme 1).…”
Section: Methodsmentioning
confidence: 99%
“…For pharmacological and biochemical properties of benzimidazole derivatives, see: Lee et al (2004); Deligeorgiev et al (2011); Scott et al (2002); Gothelf et al (1998). For related structures, see: Belaziz et al (2012); Ouzidan et al (2011). Symmetry codes:…”
Section: Related Literaturementioning
confidence: 99%
“…For their use as intermediates in chemical synthesis, see: Bai et al (2001). For similar compounds, see: Belaziz et al (2012Belaziz et al ( , 2013.…”
Section: Related Literaturementioning
confidence: 99%
“…As a continuation of our research work devoted to the development of substituted benzimidazol-2-one derivatives Ouzidan, Kandri Rodi, Fronczek et al, 2011;Belaziz et al 2012), we reported in this paper the synthesis of benzimidazol-2-one derivative by action of propargyl bromide with 1Hbenzo[d]imidazol-2(3H)-one in the presence of a catalytic quantity of tetra-n-butylammonium bromide under mild conditions to furnish two compounds: di-substituted (Ouzidan, Kandri Rodi, Jasinski et al, 2011) and mono-substituted (Scheme 1).…”
Section: Sup-1mentioning
confidence: 99%